Sobre Nome – Série de podcasts sobre os prenomes na sociedade brasileira - Messias, Morris Fabiana de (2023)
Sobre Nome” is a series of podcasts that, in three episodes, tells the relationship between nine people with their own names. Starting with characters who have unusual names, then people named after famous figures and, finally, individuals who chose to change their name after turning 18. Furthermore, the product explains how name registration is carried out in Campo Grande, Mato Grosso do Sul, and name rectification through the registry office, approved through Law 14,382 of June 2022. To create the itineraries, interviews with two psychologists, collection of information with a registry office and consumption of research based on anthroponymy, in addition to interviews with character sources. The objective is to generate reflection on name choices and relationships with this significant part of our identity, as well as to distribute information about services related to first names offered in the city's registry offices.